2004
DOI: 10.1042/bj20040524
|View full text |Cite
|
Sign up to set email alerts
|

Two related ARID family proteins are alternative subunits of human SWI/SNF complexes

Abstract: p270 (ARID1A) is a member of the ARID family of DNA-binding proteins and a subunit of human SWI/SNF-related complexes, which use the energy generated by an integral ATPase subunit to remodel chromatin. ARID1B is an independent gene product with an open reading frame that is more than 60% identical with p270. We have generated monoclonal antibodies specific for either p270 or ARID1B to facilitate the investigation of ARID1B and its potential interaction with human SWI/SNF complexes in vivo. Immunocomplex analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 30 publications
3
153
1
Order By: Relevance
“…ARID1B was found to bind to DNA without sequence specificity and is a component of BAF complexes containing either BRM or BRG1 (22,23). However, ARID1B and ARID1A are coincides with the results of previous studies.…”
Section: What Is Arid1b?contrasting
confidence: 54%
See 1 more Smart Citation
“…ARID1B was found to bind to DNA without sequence specificity and is a component of BAF complexes containing either BRM or BRG1 (22,23). However, ARID1B and ARID1A are coincides with the results of previous studies.…”
Section: What Is Arid1b?contrasting
confidence: 54%
“…This leads to dysregulation of the expression of C-MYC, delaying cell cycle entry of developmentally arrested cells, such as neural progenitors. These deficits may explain why mutually exclusive in BAF complexes (22,24).…”
Section: What Is Arid1b?mentioning
confidence: 99%
“…Two different genes encode BAF250 proteins. BAF250A (also known as OSA1 and p270/ARID1A) is encoded by ARID1A, whereas BAF250B (OSA2) is encoded by ARID1B (Hurlstone et al, 2002;Wang et al, 2004b). In addition to the ARID domains, BAF250s also contain EHD1 and EHD2 domains, which map to the C termini and mediate protein binding (Hurlstone et al, 2002).…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
“…Here we report the discovery of ARID1A as a candidate TSG in the T47D breast cancer cell line by using this approach. ARID1A encodes a human homolog of yeast SWI1, which contains a DNA-binding motif (AT-rich interactive domain, ARID) and is an integral member of the hSWI/SNF complex, an ATPdependent, chromatin-remodeling, multiple-subunit enzyme (Takeuchi et al, 1997(Takeuchi et al, , 1998Dallas et al, 1998Dallas et al, , 2000Wang et al, 2004;Wilsker et al, 2004;Patsialou et al, 2005). An increasing body of evidence has demonstrated that SWI/SNF complexes have important roles in gene regulation (Winston and Carlson, 1992;Carlson and Laurent, 1994;Hirschhorn et al, 1995;Kennison, 1995;Sudarsanam et al, 1999Sudarsanam et al, , 2000, cell proliferation (Nagl et al, 2005(Nagl et al, , 2006(Nagl et al, , 2007 and development (Carlson and Laurent, 1994;Kennison, 1995).…”
Section: Introductionmentioning
confidence: 99%